2021
DOI: 10.31450/ukrjnd.1(69).2021.07
|View full text |Cite
|
Sign up to set email alerts
|

Plasma oxalic acid as a trigger for oxidative processes in end-stage renal disease patients

Abstract: The present study aimed to evaluate the changes in oxidative stress markers according to the concentration of plasma oxalic acid (POx) in end-stage renal disease (ESRD) patients. Methods. We conducted a cross-sectional observational study involving 72 ESRD patients and 30 relatively healthy individuals who served as a control reference group for evaluation of POx concentration. Among ESRD patients there were 32 hemodialysis (HD) patients and 40 peritoneal dialysis (PD). POx concentration was measured spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
1
2
0
3
Order By: Relevance
“…In accordance with previous results, the present study demonstrated that UOx excretion or overall oxalate removal levels in all PD patients were within reference intervals for healthy subjects and similar to the previously reported average of UOx excretion in ESKD patients (3,5,6,8,13,35). Nonetheless, the levels of urine output in the participants of the present study were at least four times lower than those of healthy subjects (2,35), meaning that PD patients had hyperoxaluria.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In accordance with previous results, the present study demonstrated that UOx excretion or overall oxalate removal levels in all PD patients were within reference intervals for healthy subjects and similar to the previously reported average of UOx excretion in ESKD patients (3,5,6,8,13,35). Nonetheless, the levels of urine output in the participants of the present study were at least four times lower than those of healthy subjects (2,35), meaning that PD patients had hyperoxaluria.…”
Section: Discussionsupporting
confidence: 93%
“…Notwithstanding these limitations, our study is the first to our knowledge that reports a strong association between dialysis-related peritonitis and elevated POx in PD patients. Although the clinical significance of hyperoxalemia in PD patients remains unclear, recent studies have demonstrated that oxalate is involved in the activation of oxidative stress, chronic inflammation, and atherogenesis (1,8,9,11), which may explain the high cardiovascular and overall mortality in PD-related peritonitis. Quite possible that further research to investigate the effect of dietary oxalate restriction or the gut microbiota correction may open up a new pathway to improve PD-related peritonitis outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Подібні риси патогенезу атеросклерозу та ХХН, які включають ендотеліальну дисфункцію та хронічне запалення продемонстровані багатьма попередніми дослідженнями [6,[32][33][34][35]. Регулювання будь-якого з цих патогенетичних шляхів може пояснити визначене зниження інтраперитонеальної продукції прозапальних цитокінів у ПД пацієнтів, які приймали аторвастатин.…”
Section: плейотропні ефекти аторвастатину у пацієнтів які лікуються м...unclassified
“…ХХН у пацієнтів з ЦД може бути наслідком численних супутніх недіабетичних захворювань нирок, а саме -макросудинної ангіопатії, інтерстиціального нефриту через токсичний вплив лікарських засобів, рецидивуючої інфекції сечової системи, тощо [1,[31][32][33][34][35]. ХХН є стадійним процесом, який ініціюється впливом різноманітних екзогенних та ендогенних факторів, що приймають участь у прогресуванні ренального пошкодження з формуванням нефросклерозу [36,37]. Слід зазначити, що близько у 47% хворих на ЦД 2 типу ХХН є не діагностованою [38,39].…”
unclassified